Wholesale Energy Supplies Disruption as the Human Rights Breach: Characterisation and Causality Aspects - Oleh Zahnitko (Наукові записки НаУКМА: Юридичні науки)
This paper explores the intersection of energy security supply and human rights in Ukraine, focusing on the implications of disruptions in the supply of wholesale energy products. Ukraine’s wholesale energy sector is being under attack since early October 2023, with no legally sound reaction from the international community. The article studies, past hindrance of the economic development and personal liability caused by the attacks, the risks posed to human rights and other peremptory rules of public international law, including access to essential services, health, and an adequate standard of living. By examining the legal frameworks and international human rights standards, this study argues that sustained or significant interruptions in wholesale energy supply constitute a breach of human rights and sufficient cause of action by the Government of Ukraine under multilateral international instruments.